Critical Analysis of Humanity and Character Education Values in EFL Textbooks for Grade Ninth Students - Khoiriyah, Siti Farihatul; Said, Mashadi; E. Meidasari, Venny (INFERENCE: Journal of English Language Teaching, 2024)
This study focuses on analyzing the representation of humanity and character education values through the concept of Think Globally, Act Locally applied both in content and pedagogical approaches. The subjects of this research are Think Globally, Act Locally textbook and English for Nusantara textbook used as student guides. The study analyzes the implementation of Think Globally, Act Locally concept in both content and pedagogy and evaluates its impact on students. Using a qualitative approach through critical analysis, the findings revealed humanistic values such as truth, peace, responsibility, love, and non-violence, meanwhile character education values include religious, nationalism, appreciation, independence, and cooperation. The findings of this study not only serve as a learning tool but also as a means to foster positive social attitudes and character traits relevant to daily life. These findings also provide insights for the development of more comprehensive textbooks and strengthen character education objectives for future generations.